Lithium Ytterbium-Based Halide Solid Electrolytes for High Voltage All-Solid-State Batteries - Kim, Se Young; Kaup, Kavish; Park, Kern-Ho; Assoud, Abdeljalil; Zhou, Laidong; Liu, Jue; Wu, Xiaohan; Nazar, Linda F (ACS materials letters, 2021)
All-solid-state Li-ion batteries that utilize nonflammable solid electrolytes are considered potential candidates for sustainable energy storage systems. Although sulfide solid electrolytes have been widely explored, their lack of electrochemical stability above 2.7 V requires the application of protective coating layer on 4 V-class cathode materials, whereas the superior oxidative stability of chloride solid electrolytes enables their direct use with such high voltage cathodes. Here, we report a metastable trigonal phase of Li3YbCl6 with an ionic conductivity of 1.0 × 10–4 S·cm–1 and mixed-metal halide solid electrolytes, Li3–x Yb1–x Zr x Cl6, with conductivities up to 1.1 mS·cm–1 at room temperature. Combined neutron, single-crystal, and powder X-ray diffraction methods reveal that Zr-substitution for Yb in Li3YbCl6 triggers a trigonal-to-orthorhombic phase transition and forms new, lower energy pathways for Li-ion migration. All-solid-state cell cycling with uncoated >4 V-class cathodes is enabled by the high electrochemical oxidation stability of the mixed-metal halide solid electrolyte.